INTERNALISASI NARASI KENABIAN TENTANG RAMAH KEMANUSIAAN DALAM PENGEMBANGAN MODERASI KEAGAMAAN - Abd Fadil Abdul; Mushlihin Mushlihin; Sa’dullah Sa’dullah; Arini Susanti; Mohammad Noufal (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Islamic moderation needs to be disseminated and mainstreamed in religious life at all levels of society in order to create harmony in social life. A harmonious society is a prerequisite for the development of superior culture and civilization. Without Islamic moderation, the ummah will be deceived by the two extreme attitudes of liberalism and radicalism which will further expose them to ongoing conflicts. Islamic moderation should be a reference in responding to changes in society. The development of information and communication technology is assumed to have influenced people's behavior in all fields, including in the religious field. Human-friendly religious literacy is an effort to deal with people's behavior in using information and communication technology that seems free without any filtering. Currently, anyone can access religious sites and disseminate information without first filtering or filtering the content of that information. Thus, it can influence people's thinking and be exposed to information that contains radicalism in religion. This faculty-level community service program intends to help PAI and Islamic boarding school teachers to learn to identify, select, read prophetic narrative information about humanity-friendly. This activity has contributed to teachers in terms of having the ability to identify, select, read and understand prophetic narratives about humanity-friendly. and formulating policies that are considered important for the world of education in responding to the development of information and communication technology. This needs to be done considering that the teacher is the spearhead in educating students (santri) in teaching the good values ​​of religious teachings that are rahmatan lil alamin.